Biallelic DICER1 mutations in the gynecologic tract of mice drive lineage-specific development of DICER1 syndrome-associated cancer - Wang, Yemin; Chen, Shary Yuting; Ta, Monica; Senz, Janine; Tao, Lan Valerie; Thornton, Shelby; Tamvada, Nirupama; Yang, Winnie; Moscovitz, Yana; Li, Eunice; Guo, Jingjie; Shen, Cindy; et al. (Cancer research, 2023)
DICER1 is an RNase III enzyme essential for miRNA biogenesis through cleaving precursor-miRNA hairpins. Germline loss-of-function DICER1 mutations underline the development of DICER1 syndrome, a rare genetic disorder that predisposes children to cancer development in organs such as lung, gynecologic tract, kidney, and brain. Unlike classical tumor suppressors, the somatic "second hit" in DICER1 syndrome-associated cancers does not fully inactivate DICER1 but impairs its RNase IIIb activity only, suggesting a noncanonical two-hit hypothesis. Here, we developed a genetically engineered conditional compound heterozygous Dicer1 mutant mouse strain that fully recapitulates the biallelic DICER1 mutations in DICER1 syndrome-associated human cancers. Crossing this tool strain with tissue-specific Cre strains that activate Dicer1 mutations in gynecologic tract cells at two distinct developmental stages revealed that embryonic biallelic Dicer1 mutations caused infertility in females by disrupting oviduct and endometrium development and ultimately drove cancer development. These multicystic tubal and intrauterine tumors histologically resembled a subset of DICER1 syndrome-associated human cancers. Molecular analysis uncovered accumulation of additional oncogenic events (e.g., aberrant p53 expression, Kras mutation, and Myc activation) in murine Dicer1 mutant tumors and validated miRNA biogenesis defects in 5P miRNA strand production, of which, loss of let-7 family miRNAs was identified as a putative key player in transcriptomic rewiring and tumor development. Thus, this DICER1 syndrome-associated cancer model recapitulates the biology of human cancer and provides a unique tool for future investigation and therapeutic development.Significance: Generation of a Dicer1 mutant mouse model establishes the oncogenicity of missense mutations in the DICER1 RNase IIIb domain and provides a faithful model of DICER1 syndrome-associated cancer for further investigation.